Mental health outcomes of a pilot 2-arm randomized controlled trial of a HIV-prevention program for South African adolescent girls and young women and their female caregivers - Geri Donenberg; Katherine G. Merrill; Millicent Atujuna; Erin Emerson; Bethany Bray; Linda Gail Bekker (BMC, 2021)
Abstract Background South African adolescent girls and young women (AGYW) report significant mental distress and sexual and reproductive health concerns. Mental health problems and trauma symptoms are consistently associated with sexual and reproductive health behavior. Despite their intersection, few interventions address them simultaneously or engage female caregivers (FC) as collaborators. This study presents findings from a pilot test of an empirically supported culturally adapted family-based HIV-prevention program, Informed Motivated Aware and Responsible Adolescents and Adults- South Africa (IMARA-SA), on AGYW anxiety, depression, and trauma. Methods Sixty 15-19-year-old AGYW (mean age = 17.1 years) and their FC from outside Cape Town were randomized to IMARA-SA or a health promotion control program. AGYW reported their anxiety using the GAD-7, depression using the PHQ-9, and trauma using the PC-PTSD-5 at baseline and follow-up (6-10 months post). Both interventions were delivered by Xhosa-speaking Black South African women in groups over 2 days for approximately 10 h. We examined intervention effects using zero-inflated negative binomial regression for anxiety, multinomial logistic regression for depression, and logistic regression for trauma. Results At baseline, groups did not differ in demographic characteristics but AGYW randomized to IMARA-SA had higher depression scores than controls (p = 0.04) and a greater proportion screened positive for PTSD (p = .07). Controlling for baseline mental health scores, AGYW who received IMARA-SA compared to controls had significantly fewer anxiety symptoms at follow-up (adjusted incidence rate ratio for count model = 0.54, 95% CI = 0.29-0.99, p = 0.05), were less likely to report at least one depressive symptom relative to no symptoms (relative risk ratio = 0.22, 95% CI = 0.05, 0.95, p = 0.04), and were less likely to report symptoms of PTSD relative to no symptoms, but this difference was not statistically significant. Conclusions Mental health is implicated in risky sexual behavior, and reducing emotional distress can mitigate exposure to poor sexual and reproductive health outcomes. This pilot study yielded promising findings for the mental health impact of IMARA-SA, justifying replication in a larger randomized trial. Trial registration ClinicalTrials.gov Number NCT04758390 , accepted 17/02/2021.